Effect of Polymer Mixtures on Physical-Chemical Properties of Sandy Soil and Plant Growth - Yang, Qingwen; Pei, Xiangjun; Fu, Cheng (Frontiers in Ecology and Evolution, 2022)
Grassland degeneration of Qinghai-Tibet Plateau is getting worse, the rehabilitation progress of degraded grassland is slow under natural conditions. In this study, through pot experiments, the plant's growth and development, as well as the physical, chemical, and biological characteristics of the root-zone soil were monitored for 7 months in the experimental group added with modified organic materials (M-CMC) and the control group, it is found that the aboveground biomass of plants in the experimental group is increased by 59.65%, lodging rate decreased by over 60%, drought tolerance, and survival rate rises by more than 80%. Besides, the number of plant roots in the experimental group was at least two times greater than the control group, indicators like RAR, RAI, and Rv are one time greater, which means that M-CMC could effectively promote the plant root development, improve the plant drought tolerance and lodging resistance. Compared with the matched group, the rhizosphere soil mass, root-zone soil mass and soil crust thickness of experimental group are 1.84 times, 2.63 times and 1.96 times respectively, which means that M-CMC have strengthened the root soil fixation ability and soil crusting ability of plants. In the experimental group, The SOM, TN and AP (soil nutrient indicators) increased by 27.45%, 17.97% and 35.38%, respectively, sucrase, protease and catalase (soil enzyme activity indicators) increased by 22.73%, 33.33% and 14.29%, respectively. MBN and MBC (soil microbial activity index) increased by 15.91% and 12.37%, indicating that M-CMC has obvious maturation effect on plant root-zone soil. A quantitative model is established to describe these changes. The mechanism of succession fixation soil by M-CMC and plant root is revealed, which provides effective materials for the restoration of desertified grassland in Qinghai-Tibet Plateau.